Lung herniation into pericardial cavity: A case of partial congenital absence of right pericardium - Sadashiv B Tamagond; Saket Agarwal; Akhilesh S Tomar; Deepak K Satsangi (Wolters Kluwer Medknow Publications, 2012)
Congenital absence of pericardium is rarely seen, often diagnosed intraoperatively during cardiac and thoracic surgeries. Left-sided pericardial defects are more common than right-sided ones. We present a case of an incidentally detected congenital absence of right pericardium with herniation of part of the right lung during ventricular septal defect closure surgery in a male child aged 4 years.